Salt content in ready to eat soups in Portugal - Comparison between 2018 and 2019 - Fernandes, Paulo (2021)
Objectives: To verify the evolution of salt content of ready to eat soups, on Portuguese market between 2018 and 2019, through labelling information and its compliance with EIPAS goal of 0.2 g of salt / 100 g.